2015
DOI: 10.1103/physreva.91.043634
|View full text |Cite
|
Sign up to set email alerts
|

Strongly interacting quantum gases in one-dimensional traps

Abstract: Under second-order degenerate perturbation theory, we show that the physics of N particles with arbitrary spin confined in a one-dimensional trap in the strongly interacting regime can be described by superexchange interaction. An effective spin-chain Hamiltonian (non-translationally-invariant Sutherland model) can be constructed from this procedure. For spin-1/2 particles, this model reduces to the non-translationally-invariant Heisenberg model, where a transition between Heisenberg antiferromagnetic (AFM) an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 57 publications
(105 reference statements)
2
100
0
Order By: Relevance
“…This is particularly true for the system of repulsive polaron, since it lies in an excited upper branch of atomic system rather than the ground state. On the other hand, one might be able to gain important insights by studying the counterpart problem in 1D, where the exact solutions can be accessible [21] and effective spin-chain models can be established in strong coupling limit [22][23][24][25][26][27][28]. For 1D fermion system, the ferromagnetic transition has been exactly proved with arbitrary number and arbitrary potential [29], and the polaron problem in continuum has also been exactly solved by McGuire in 1960's [30,31] and recently by Guan [32].…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for the system of repulsive polaron, since it lies in an excited upper branch of atomic system rather than the ground state. On the other hand, one might be able to gain important insights by studying the counterpart problem in 1D, where the exact solutions can be accessible [21] and effective spin-chain models can be established in strong coupling limit [22][23][24][25][26][27][28]. For 1D fermion system, the ferromagnetic transition has been exactly proved with arbitrary number and arbitrary potential [29], and the polaron problem in continuum has also been exactly solved by McGuire in 1960's [30,31] and recently by Guan [32].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, various spin-chain Hamiltonians can be constructed in response to different external perturbations, including interactions, gauge fields and trapping potentials, which have been used to address and engineer novel spin spirals and magnetic orders in 1D systems [12][13][14][15][16][17][18][19][20][21][22][23][24]. Experimentally, an anti-ferromagnetic spin chain has been recently confirmed in a small cluster of 1D trapped fermions [25].…”
Section: Fig 1 (Color Online)mentioning
confidence: 99%
“…Following this idea one can construct various spin chain models as studied in the literature [12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, taking advantage of the high controllability of a few particles in the trapped ultra-cold systems [20], a number of studies have revealed the energy spectra and correlation effects for a few spin-1/2 fermions by numerical simulations [21][22][23][24]. In the strong coupling regime, an effective Heisenberg spin-chain model has also been deduced [25][26][27][28]. The resulted anti-ferromagnetic correlation has recently been confirmed through the tunneling measurement of a few spin-1/2 fermions in 1D traps [29].…”
mentioning
confidence: 99%